"Căluş and căluşari": ceremonial syntax and narrative morphology in the grammar of the romanian "căluş" - Neagotă, Bogdan (Archaeus, 2010)
Bringing forth the Romanian Calus in a context of sacred and magical medicine can pass for a two-bladed sword: on the one hand, it asserts the existence of a specific affliction, of meta-mundane etiology; while on the other hand, it states that there is a ritual institution responsible for the cure. As we shall demonstrate in the pages below, this equation is but a dimension to the multifarious phenomenon the Calus is. Whether or not it is a vital dimension, testifying about ceremoniality within folkloric European societies, as answer to institutionalized disruptions over internal rhythms, this stays one of our core theoretical preoccupations. Always at the core, we hold the articulation of narrativity and ceremoniality of a same ritual/mythical/religious complex, in the course of its trans- and inter-generational transmission. We endeavor here to address these questions, as applied to Calus, on several explanatory levels, as follows: the narrative threshold of approaching the Calus, and its availibility for the ethnologist; the mythical-fictional nature of field narratives, about the specific ailment and healing contained within this tradition; the incidence of the dramatized ceremonial within the year cycle, and finally, the cure the Calus engenders: descriptively, analogically, differentially